Epidemiology of Mycoplasma pneumoniae Infections in Japan and Therapeutic Strategies for Macrolide-Resistant M. pneumoniae - Yamazaki, Tsutomu; Kenri, Tsuyoshi (Frontiers in Microbiology, 2016)
Pneumonia caused by Mycoplasma pneumoniae (M. pneumoniae pneumonia) is a major cause of community-acquired pneumonia worldwide. The surveillance of M. pneumoniae pneumonia is important for etiological and epidemiological studies of acute respiratory infections. In Japan, nation-wide surveillance of M. pneumoniae pneumonia has been conducted as a part of the National Epidemiological Surveillance of Infectious Diseases (NESID) program. This surveillance started in 1981, and significant increases in the numbers of M. pneumoniae pneumonia patients were noted in 1984, 1988, 2006, 2010, 2011, 2012 and 2015. The epidemics in 2011 and 2012 were particularly widespread and motivated researchers to conduct detailed epidemiological studies, including genotyping and drug resistance analyses of M. pneumoniae isolates. The genotyping studies based on the p1 gene sequence suggested that the p1 gene type 1 lineage has been dominant in Japan since 2003, including the epidemic period during 2011-2012. However, more detailed p1 typing analysis is required to determine whether the type 2 lineages become more relevant after the dominance of the type 1 lineage. There has been extensive research interest in implications of the p1 gene types on the epidemiology of M. pneumoniae infections. Serological characterizations of sera from patients have provided a glimpse into these associations, showing the presence of type specific antibody in the patient sera. Another important epidemiological issue of M. pneumoniae pneumonia is the emergence of macrolide-resistant M. pneumoniae (MRMP). MRMPs were noted among clinical isolates in Japan after 2000. At present, the isolation rate of MRMPs from pediatric patients is estimated at 50–90% in Japan, depending on the specific location. In view of the situation, Japanese societies have issued guiding principles for treating M. pneumoniae pneumonia. In these guiding principles, macrolides are still recommended as the first-line drug, however, if the fever does not subside in 48–72 hours from first-line drug administration, a change of antibiotics to second-line drugs is recommended.